System Development Life Cycle As A Model of Electronic Design Business Latif Distro - Rahma Karlinda; Ahmad Latif Saifulloh (Dinar Islamic Review, 2022)
Competition in the field of business is increasingly sophisticated in line with the development of information technology at this time can create business opportunities for traders to make online sales. With the online technology of the merchants it is easy to conduct transactions without having to go to the desired place of sale. Internet facilities support sellers to make online sales. But the facilities used to connect the Internet network on Latif Distro are not yet available, for it will be designed an online sales program using photoshop, macromedia dreamweaver, php mysql and Xampp, Making this Application is done by observation and Interview method and then designed with the System Development Life Cycle (SDLC) model. With the design of web-based sales is expected to help and attract customers and help increase sales in the Latif Distro. Facilitate consumers in shopping without having to come to the place of direct sales simply by online anytime and anywhere.